KONSEPSI ALQURAN TENTANG MANUSIA - Santoso Irfan (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with the conception of the Qur’an on human beings. One of the major themes of the Qur’an is concerned  with human beings and their functions on the earth. The Qur’an speaks of  human beings  in various terms such as al-insan, al-basyar, -‘abd and khalifah. The term Al-insan refers to the quality of thought and consciousness of human beings’; al-basyar signs their natural dimensions such as eating, drinking and dying; ‘abd  indicates their obedience and  piety, and khalifah denotes  their freedom and creativity.Kata Kunci : Alquran, manusia, al-insan, al-basyar, ‘abd,   khalifah